Healthcare Commodity Logistics Management Systems: A Review - Omeh, Romanus (Indian Journal of Pharmacy Practice)
Health commodities are critical and indispensable component of the total healthcare package needed to deliver quality healthcare to patients and communities. Effective delivery of healthcare will hardly be possible without drugs (medicines) surgical consumables, palliative materials and other items like diagnostic kits, medical laboratory chemicals, reagents and other sundry patient care commodities. Good knowledge and competence in the management of health commodities is important for health practitioners who are often the custodians of such products. Unfortunately, the study of commodity logistics and management in the health-based faculties of many universities especially in the developing nations is either completely lacking or do not receive adequate credit loads. The purpose of this review is to present in a narrative manner the basic concepts and language of logistics and commodity management, for the benefit of the Pharmacy and other health discipline teachers, students, practitioners and researchers. The introductory part of the work briefly reviewed the history and definitions of logistics as wells as some basic concepts encountered in health commodity logistics practices Attention was also devoted to some functional concepts and tools used in commodity management especially in health facilities. The expanding roles of logistics and commodity management in waste management, reverse logistics, green environment and effective healthcare services delivery were also reviewed. The simplicity and rudimentary approach and language employed in the review will likely stimulate the understanding and interest of the readers and researchers in the subject of commodity logistics and logistics management systems.
Keywords: Commodity; Logistics management; Inventory management; Supply chain management; Stock statues; Green logistics; Reverse logistics.